Optical technique of investigation of the structural changes of aluminun polycrystals - Badiyan, E.E.; Tonkopryad, A.G.; Shekhovtsov, O.V.; Shurinov, R.V. (Functional Materials, 2006)
An in situ technique has been proposed to observe structural changes of an alumininum polycrystal during plastic straining based on white light scattering by the previously etched sample surface. It is shown that a quasi-periodic relief of grain surface results from the chemical etching, the character of such relief is defined by crystallographic orientation of each grain. The white light scattering by the surface relief causes coloring of grains which is recorded using a Web-camera. It is shown in experiment that a change in crystallographic orientation of grains or their fragments during the plastic straining of two-dimensional aluminum polycrystals is accompained by coloring change thereof.